2021
DOI: 10.2478/popets-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

OmniCrawl: Comprehensive Measurement of Web Tracking With Real Desktop and Mobile Browsers

Abstract: Over half of all visits to websites now take place in a mobile browser, yet the majority of web privacy studies take the vantage point of desktop browsers, use emulated mobile browsers, or focus on just a single mobile browser instead. In this paper, we present a comprehensive web-tracking measurement study on mobile browsers and privacy-focused mobile browsers. Our study leverages a new web measurement infrastructure, OmniCrawl, which we develop to drive browsers on desktop computers and smartphones located o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…AutoFR can also be applied to other platforms, such as mobile, smart TVs, and VR devices, as there is need for better platform-specific filter lists, in terms of coverage and breakage [72,82,84]. On mobile and Smart TVs specifically, we could leverage existing tools to automatically explore apps or mobile browsers [17,50,72,84]. Finally, AutoFR can also be used to maintain and improve existing filter lists over time, not only to generate them from scratch.…”
Section: Discussionmentioning
confidence: 99%
“…AutoFR can also be applied to other platforms, such as mobile, smart TVs, and VR devices, as there is need for better platform-specific filter lists, in terms of coverage and breakage [72,82,84]. On mobile and Smart TVs specifically, we could leverage existing tools to automatically explore apps or mobile browsers [17,50,72,84]. Finally, AutoFR can also be used to maintain and improve existing filter lists over time, not only to generate them from scratch.…”
Section: Discussionmentioning
confidence: 99%
“…Equivalent amount of ads/trackers traffic. To assess the amount of trackers and advertisers in traffic, we use the same approach as previous works [5,14,41]: use the EasyList and EasyPrivacy blocklists 10 to identify trackers. Our results show that WPM and WPM hide encounter a near equal rate of advertisers and trackers.…”
Section: Evaluation Of Poc Implementationmentioning
confidence: 99%
“…This relies on an (often unstated) assumption that the data as collected is representative of what a regular, human-controlled browser would encounter. Previous works [5,14,39,41] have shown that this is not always the case: websites have been found to omit content (advertisements, video, JavaScript execution, login forms, etc.) or require completion of a CAPTCHA for automated clients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations